Spectrum of Disease Caused by Rhodococcus equi in Human Immunodeficiency Virus Infection: Report of a Case and Review of the Literature - Sandra K Willsie-Ediger; James F Stanford; Gary A Salzman; David M Bamberger (Canadian Journal of Infectious Diseases)
Since the first report of Rhodococcus equi infection in an acquired immune deficiency syndrome patient in 1986, seven additional cases have been described. A patient is described in whom the diagnosis was delayed due to misidentification of the organism as an atypical mycobacterial species. The literature regarding R equi infection in persons infected with the human immunodeficiency virus is reviewed. The most common presentation is one of a chronic, indolent pulmonary infiltrative disease (78%). Fever (78%), cough (67%), and hemoptysis (44%) are frequently present. Coexistent opportunistic illnesses are common (67%). In the laboratory identification of this organism, it is important to communicate the clinical setting to the microbiologist and to recognize the potential for the organism to be overlooked as normal flora or a contaminant, or misidentified as an organism with similar phenotypic characteristics (Nocardia species or a rapidly growing mycobacterium). Based on experience in foals, therapy with erythromycin and rifampin is suggested.